2017
DOI: 10.5897/ijps2016.4595
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemical investigation and characterization of shallow groundwater within Ankpa Town, North Central Nigeria

Abstract: Physico-chemical analysis of groundwater samples from Ankpa, north central Nigeria was carried outto investigate the quality of the water for drinking and irrigation purposes. The results revealed water of average low pH, indicating slightly acidic conditions of the water. The water is soft, and it is characterized as Na + +K -HCO 3 type. It is good for drinking and other domestic uses. Four indices were evaluated from the groundwater chemistry in order to establish the suitability of the water for irrigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The trend of the Ca 2+ + Mg 2+ water type in a straight line on the Piper diagram (figure 6) is an indication of a solution or precipitation. The source of the HCO − 3 + CO − 3 water type is rainfall mixed with atmospheric carbon dioxide, usually low in calcium and magnesium and is said to be juvenile water (Akpah et al 2017). The Stiff pattern diagrams showed similar patterns for all samples with the exception of samples 8, 15 and 17.…”
Section: Water Typementioning
confidence: 98%
See 4 more Smart Citations
“…The trend of the Ca 2+ + Mg 2+ water type in a straight line on the Piper diagram (figure 6) is an indication of a solution or precipitation. The source of the HCO − 3 + CO − 3 water type is rainfall mixed with atmospheric carbon dioxide, usually low in calcium and magnesium and is said to be juvenile water (Akpah et al 2017). The Stiff pattern diagrams showed similar patterns for all samples with the exception of samples 8, 15 and 17.…”
Section: Water Typementioning
confidence: 98%
“…It showed that 23.33% of water samples are good, permissible and doubtful, respectively, while 16.67% are excellent and 13.34% are unsuitable for irrigation. Low Na + water can be used for irrigation on all soils with minimal danger of harmful exchangeable Na + developing (Singh et al 2009), while on the other hand, high sodium water in most soils will require special soil management, such as good drainage, high leaching and organic matter as it produces harmful exchangeable sodium (Akpah et al 2017). High Na% in water will result in the replacement of Mg 2+ and Ca 2+ by Na + which impedes soil permeability, reduces soil drainage, affects soil structure and aeration and therefore, affects plant growth (Singh et al 2008(Singh et al , 2009Akpah et al 2017).…”
Section: Water Quality For Irrigationmentioning
confidence: 99%
See 3 more Smart Citations